10 years of affirmative actions for indigenous persons in the UESB: a reading based on institutional data - Pinto, Danilo César Souza; Cerqueira de Jesus, Francislene (ODEERE, 2023)
It has been one decade since the affirmative actions were implemented in Brazil, and the State University of Southwestern Bahia has been promoting them since 2009. Over these first 10 years, dozens of indigenous persons entered and graduated from this institution. Our goal is to reflect on such context based on institutional data by establishing comparisons with other segments that also access the university, as well as data from other higher education institutions. Despite the policy and good academic performance, the number of indigenous persons who benefit from it still remains below the offer and is particularly concentrated in some courses in the health field.